Research on Industrial Product Design under the Zero Carbon Concept - Zhou Ziru; Zhong Qinghua (E3S Web of Conferences, 2023)
In the context of modernisation, as the state advocates green consumption in various fields, the concept of green consumption continues to influence the public’s consumption philosophy and more and more consumers are gradually moving towards green consumption. The essence of the green consumption concept lies in the high regard that humans have for the natural ecological environment and the pursuit of sustainable development, while zero carbon is the embodiment of ecological and sustainable lifestyles. From a global perspective, the concept of zero carbon is becoming an indispensable tool for companies to achieve profitability, competitiveness and healthy and stable development. With this in mind, we have investigated the design of industrial products based on the zero carbon concept in the hope of contributing to the social and economic shift towards zero carbon.